PERBEDAAN TINGKAT KECEMASAN PRE DAN POST OPERASI DI BANGSAL BEDAH KENANGA RSUD PROF. DR. MARGONO SOEKARJO PERIODE 1-5 OKTOBER 2012 - Budi Setyaningsih, Tri Rini; SS, Meirina; RN, Ria; RH, Amanda; YR, Gita; YR, Gina (MANDALA of Health, 2013)
Anxiety is one of manifestation that can occur to surgery patients. This research aims to find out the level of anxiety pre and post surgery in Kenangaâs ward of Prof. Dr. Margono Soekarjo Hospital. The method of this research is a quasi experimental with one group pre post test design approach. The samples of this research are all of the surgery patients in Kenangaâs ward during October 1st to 5th, 2012, by 42 participants. The data analythics used univariate and bivariate paired simple T test. The results showed there is a difference between anxiety level pre and post surgery (p < 0,05).